Improving use of statistical information by jurors by reducing confusion of the inverse - Raacke, John David (Kansas State University, 2005)
In many situations, people are called on to make judgments about the likelihood of an event. Research has shown that when people make these judgments, they frequently equate or confuse conditional probabilities with other conditional probabilities. This equating or confusing of conditional probabilities is known as the confusion of the inverse. Research investigating this problem typically focuses on clinical and medical decision-making and the use of statistical evidence to make diagnoses. However, one area in which the confusion of the inverse has not been studied is in juror decision-making. Thus, the purpose of this dissertation was to (1) determine if the confusion of the inverse influences juror decision-making, (2) interpret reasons why this confusion occurs, and (3) attempt to eliminate it from juror decision-making. Jurors were presented with four court cases gathered from local and federal courthouses in a small Mid-western city. In each of the four cases, a single piece of evidence was presented (statistical only) which was to be used when rendering verdicts. Finally, each case contained juror instructions for the specific case type: murder, kidnapping, arson, sexual assault. Overall, jurors fell prey to the confusion of the inverse, equating the probability of the data given the hypothesis [P(D|H)] with the probability of the hypothesis given the data [P(H|D)]. However, the research was unable to reduce the effect, much less eliminate it from the task. Interestingly, jurors tended to ignore the statistical evidence (i.e., estimations about probability of a match) in favor of their own personal believe in the strength of the evidence. Although the original intent of reducing/eliminating the confusion of the inverse was not accomplished, the dissertation did accomplish three things. First, researchers have hypothesized three reasons why people engage in incorrect probabilistic reasoning, and the dissertation affirmed that it is indeed a function of the confusion of conditional probabilities – the confusion of the inverse. Second, it seems that the use of statistical evidence in a trial is ignored by most jurors in favor of their own personal belief in the evidence’s strength. Finally, the criteria needed for “beyond a reasonable doubt” may be too stringent.
Keywords: Juror decision-making; Confusion of conditional probablities; Psychology, General (0621)